Variabilidade genética e de compostos voláteis e semi-voláteis em Maytenus ilicifolia Mart. ex Reiss - Mossi, Altemir José (2003)
Genetic and chemical variability of Maytenus ilicifolia Maytenus ilicifolia is a native plant of Southern Brazil commonly used as a popular medicine for indigestion, gastritis and ulcers. The large use of this plant has increased the degradation of the species, and thus it is presently included in FAO´s list for priority species for studying and conservation in South America. In this context, this work aimed to contribute with studies that help the conservation of this species. Initially, a survey in herbaria and in the field was performed to identify the incidence and distribution of the genus Maytenus in the State of Rio Grande do Sul. Three new species (M. glaucenscens Reiss, M. gonoclada Mart. and M. robusta Reiss) were found in this State. The genetic variability study of three populations showed that the intrapopulational variation (variance from 0.102 to 0.140) is higher than the interpopulational (variance between 0.076 and 0.099%). The three populations analyzed grouped themselves with low significance level and 7.6% of the present alleles are rare. The genetic variability study involving 18 native populations of Maytenus ilicifolia, Maytenus aquifolia and Maytenus evonymoidis demonstrated that the species may be separated with 100% of confidence, and that M. ilicifolia and M. aquifolia are genetically more similar. The populations of Maytenus ilicifolia analyzed formed three groups with low confidence levels. Group I included the populations of Ponta Porã, group II the populations of Santana do Livramento, Vale Verde, Canguçu and Unistalda, and group III was formed by the other 13 populations. A similarity in the genetic and environmental grouping of such species was observed. The chemical characterization was performed by gas chromatography of the extracts obtained with high pressure CO2. An increase in the yield of extract was obtained when the temperature of extraction as well as the solvent density were increased. The compounds that presented higher yield in the first fractions were dodecanoic acid, geranyl acetone, phytol, squalene, vitamin E and stigmast-5-enol. The compounds friedelan-3-ol and friedelin were extracted in higher yields in the following fractions. The chemical variability study of the volatile and semi-volatile compounds of populations of M. ilicifolia showed a yield of extract (0,488 a 0,976 %) significantly different between the populations. In addition no relation between the chemical and environmental or between the chemical and genetic grouping could be established.